2015
DOI: 10.1371/journal.pone.0129909
|View full text |Cite
|
Sign up to set email alerts
|

Role of Transthoracic Lung Ultrasonography in the Diagnosis of Pulmonary Embolism: A Systematic Review and Meta-Analysis

Abstract: BackgroundPulmonary embolism (PE) is a potentially life-threatening condition. Although computed tomography pulmonary angiography (CTPA) is the reference standard for diagnosis, its early diagnosis remains a challenge, and the concerns about the radiation exposures further limit the general use of CTPA. The primary aim of this meta-analysis was to evaluate the overall diagnostic accuracy of transthoracic lung ultrasound (TLS) in the diagnosis of PE.MethodsPubMed, Web of science, OvidSP, ProQuest, EBSCO, Cochra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 50 publications
0
21
0
2
Order By: Relevance
“…11 For the diagnosis of pulmonary embolism, another potential etiology of alveolar syndrome, LUS may show peripheral infarcts, but alone does not have adequate accuracy when compared with CT [sensitivity 85% (95% CI, 78 to 90%), specificity 83% (73 to 90%)]. 67 Nevertheless, LUS still represents a valid alternative diagnostic tool when CT cannot be performed or is contraindicated. 60 Moreover, an integrated multiorgan approach using focused cardiac, lung, and venous ultrasonography has been shown to achieve significantly higher diagnostic accuracy for pulmonary embolism (sensitivity 90%, specificity 86.2%).…”
Section: Alveolar Syndromementioning
confidence: 99%
“…11 For the diagnosis of pulmonary embolism, another potential etiology of alveolar syndrome, LUS may show peripheral infarcts, but alone does not have adequate accuracy when compared with CT [sensitivity 85% (95% CI, 78 to 90%), specificity 83% (73 to 90%)]. 67 Nevertheless, LUS still represents a valid alternative diagnostic tool when CT cannot be performed or is contraindicated. 60 Moreover, an integrated multiorgan approach using focused cardiac, lung, and venous ultrasonography has been shown to achieve significantly higher diagnostic accuracy for pulmonary embolism (sensitivity 90%, specificity 86.2%).…”
Section: Alveolar Syndromementioning
confidence: 99%
“…A meta‐analysis of conventional transthoracic lung ultrasonography for the diagnosis of pulmonary embolism of 1356 patients in 13 reported studies showed that sensitivity was 0.85, specificity was 0.83, positive likelihood ratio was 5.09, negative likelihood ratio was 0.18, diagnostic odds ratio was 28.82, and hierarchical summary receiver‐operating characteristic curve was 0.91. The conclusions of this meta‐analysis were that “Although the application of transthoracic lung ultrasound may change some patients' diagnostic processes, it is inappropriate to generally use transthoracic ultrasonography in diagnosing pulmonary embolism currently.”…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining this sonographic finding have focused on populations with a high pre-test probability of PE. Systematic reviews [50,51] report inferior sensitivity to gold-standard CT pulmonary angiography (CTPA) ( Table 1), with one reporting a false negative rate of 11% in patients with a high pre-test probability of PE [51]. Given the grave consequences of a false negative result, chest ultrasound alone is not recommended in place of CTPA, although it may suggest alternate diagnoses in this population [52].…”
Section: Pulmonary Embolismmentioning
confidence: 99%